Song-Powered Learning: Enhancing Vocabulary and Reading Comprehension of Junior Bael Students - Tiarra Lynn Bayongasan; Judelyn Alones; Elaika Mae Flores (Universitas Kapuas, 2026)
The study examined the effects of classical, jazz, rock, and pop background music on the vocabulary and reading comprehension performance of BAEL students. Despite research on music-assisted language learning, there is limited research integrating affective factors and cognitive outcomes, such as vocabulary retention and reading comprehension, among university-level English majors. A quasi-experimental pretest–post-test design was employed, involving four intact classes assigned to different music conditions. Paired-samples t-tests were used to analyze prepost differences in vocabulary and reading comprehension. Results of the study showed significant differences in post-test scores across groups, with classical, jazz, and rock music yielding significant gains, while pop music showed no significant improvement. The classical group obtained the highest post-test performance, followed by jazz and rock, whereas the pop group recorded the lowest gain. T-test results indicated statistically significant differences between pre-test and post-test scores for the classical, jazz, and rock groups, but not for the pop group. Item-level analysis further showed consistent difficulty in abstract, low-frequency vocabulary and inferential reading comprehension across all groups. Overall, the findings indicate that background music can support vocabulary and reading development when aligned with cognitive demands, highlighting the pedagogical value of carefully selected music in tertiary language classrooms.